Communal Violence, Mental Health and Their Correlates: A Cross-Sectional Study in Two Riot Affected Districts of Uttar Pradesh in India - Farooqui, Neelo (Journal of Muslim minority affairs, 2021)
Communal violence in India has become more frequent due to the unwanted interplay between religion and political manipulation, by which India has been affected many times. Communal violence has also been recognized as a significant social and public health problem, resulting in long-term human and economic costs. The dominant form of communal violence in India has involved the two communities, i.e. Hindus and Muslims. Post-violence studies worldwide have shown a short and long-term higher prevalence of mental health disorders. To the best of our knowledge, no earlier study has investigated the association between communal violence experience and self-rated psychological health in India. Thus, the current study was designed to provide valuable addition to the existing literature on mental stress among riot victims. This paper explores the association between mental health and socio-economic characteristics among riot victims based on a primary survey (N = 300 participants) conducted in two riots-affected districts of Uttar Pradesh in India.